2018
DOI: 10.1021/acs.molpharmaceut.7b00843
|View full text |Cite
|
Sign up to set email alerts
|

Ratio-Dependent Synergism of a Doxorubicin and Olaparib Combination in 2D and Spheroid Models of Ovarian Cancer

Abstract: Ovarian cancer is the fourth leading cause of death in women in developed countries. Even though patients with the most lethal form of the disease (HGSOC; high grade serous ovarian cancer) respond well to initial treatment, they often relapse with progressively resistant disease. Inhibitors of the poly(ADP-ribose) polymerase (PARP) enzymes are a relatively new class of molecularly targeted small molecule drugs that show promise in overcoming resistance. The present study explores the combination of a DNA damag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 67 publications
(182 reference statements)
7
29
1
Order By: Relevance
“…Fig). Therefore, carboplatin sensitivity was evaluated in 3D spheroids formed in the PDMS microfluidic device and the Matrigel-assisted ULA plate since the latter is widely used for drug sensitivity assays [11,18,19,45,50].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Fig). Therefore, carboplatin sensitivity was evaluated in 3D spheroids formed in the PDMS microfluidic device and the Matrigel-assisted ULA plate since the latter is widely used for drug sensitivity assays [11,18,19,45,50].…”
Section: Discussionmentioning
confidence: 99%
“…In the particular case of ovarian cancer, 3D spheroids are clinically relevant models since in advanced disease EOC cells can spread to the peritoneum as aggregates/spheroids [52,53]. In the literature, several EOC cell lines have been studied by different spheroid generating methods, including hanging-droplets [16, 22, 27-29, 41, 54, 55], biomimetic hydrogels [23], plastic wells coated with matrix scaffolds [20,46,56], and more recently by microfluidics [33,34,37,38,42,44] and commercially available round-bottom ULA plates [18,45,50,57]. In the present study we first compared the ability of four EOC cell lines to form spheroids using these ULA 96-well plates (in the absence or presence of Matrigel) with that of hanging-droplets and PDMS-based microfluidic chips.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, a preclinical study demonstrated a synergism of the combination of olaparib with doxorubicin in 2D and spheroid models of ovarian cancer [14]. This study showed that DNA damage was increased at a molar concentration of doxorubicin: olaparib of 50:1 in both BRCA mutant and BR CA wild type cell lines UWB1-289.…”
Section: The Rolando Trialmentioning
confidence: 99%